PUBLIC–PRIVATE PARTNERSHIPS IN HOUSING CONSTRUCTION IN UKRAINE - Balabenko, Elena (Ekonomika, 2014)
Abstract. The paper presents an analysis of construction operations, retarding tendencies, necessity to attract private capital to civil engineering, with an emphasis on the development of national cooperation and con- struction business in the realization of concrete social and economic and investment projects in Ukraine in the form of public–private partnership. The problems of the development of housing construction institutions are also presented within the framework of the public–private partnership and the preconditions for the topical character of the private capital attraction to this sphere. The necessity of developing the public–private partnership in housing construction has been justified. The development of the trend will help to unify the interests of power, business, financial institutions and private investors. Also, a special pattern of the public–private partnership taking into consideration the peculiarities of the contemporary house-building industry is proposed. Key words: housing construction, public–private partnership, investment, pattern